2006
DOI: 10.1007/bf02934745
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indexes of septic syndrome in the emergency department

Abstract: Among critical patients admitted to an Italian ED, those with severe sepsis/septic shock represent about 1%, with a very high mortality rate. Bedside non-invasive prognostic indexes are able to identify with high accuracy patients with adverse short-term clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The sample size was variable. There were six studies that recruited fewer than 100 patients (29,31,35,(39)(40)(41). Only three studies included more than 2000 patients (23,25,34).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The sample size was variable. There were six studies that recruited fewer than 100 patients (29,31,35,(39)(40)(41). Only three studies included more than 2000 patients (23,25,34).…”
Section: Resultsmentioning
confidence: 97%
“…All the 21 articles included were cohort studies, 15 were prospective and six retrospective [ (13,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) and (37)(38)(39)(40)(41)(42), respectively]. The study population in 15 of the articles was defined by the fulfillment of two or more SIRS criteria (13,24,(27)(28)(29)(30)32,33,(35)(36)(37)(39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be hypothesized that patients with a history of diabetes are more likely to receive intensive insulin treatment during their stay. In a recent paper by Giannazzo et al [26] (and in the Editorial by Ban et al [27]), in a retrospective study performed in patients admitted to the ED with a diagnosis of severe sepsis or septic shock, some therapy with insulin is the only variable related to a lower risk of death and, at univariate analysis, a history of diabetes predicts a favorable outcome. This phenomenon may be related to the fact that diabetics are treated earlier and much more aggressively since they are easily recognized as being at a higher risk of sepsis.…”
Section: Prevalence and Prognostic Value Of Hyperglycemiamentioning
confidence: 97%
“…Our recent data has shown that patients with severe sepsis or septic shock represent 0.2% of all incoming patients to a tertiary care European ED, showing a 51% mortality rate at 28-dayfollow up. Bedside prognostic indexes are useful in the recognition of patients at high risk for adverse short-term outcome [3]. In particular serum lactate ([5 mmol/L) is found to be significantly related to death within 24 h after admission.…”
Section: Dr G Pepementioning
confidence: 99%